Impact of ankylosing spondylitis on foot health and quality of life: an observational case–control study. - Cortés-Rodríguez, Antonio; Alves-Gomes, Lisa; Losa-Iglesias, Marta Elena; Gómez-Salgado, Juan; Becerro-de-Bengoa-Vallejo, Ricardo; Saavedra-García, Miguel; Montiel-Luque, Alonso; López-López, Daniel; Jiménez-Cebrián, Ana María (Frontiers, 2024)
Background: Ankylosing spondylitis (AS) is a chronic, inflammatory, and autoimmune disease. This condition primarily affects the axial skeleton and presents direct foot involvement, such as Achilles enthesitis or plantar fascia involvement. Objective: This study aimed to investigate the impact of foot health on the quality of life of individuals with AS compared to a control group without AS. Materials and methods: A sample of 112 subjects was recruited, with a mean age of 46.80 ± 10.49 years, divided into two groups: 56 individuals with AS (cases) and 56 individuals without AS (controls). Demographic data were collected, and the scores obtained in the Foot Health Status Questionnaire domains were recorded.Results: Of the participants, 27.79% (N = 30) were men and 73.21% (N = 82) were women. The mean age in the group was 46.80 ± 10.49. Significant differences (p < 0.05) were found in the domains of foot function, foot pain, footwear, overall foot health, general health-related physical activity, and social capacity between the AS group and the control group. Conclusion: Individuals with AS exhibited a decreased quality of life, as indicated by their Foot Health Status Questionnaire scores.
Keywords: Espondiloartropatías; Pie - Anomalías y malformaciones; Pie - Enfermedades; Ankylosing spondylitis; Foot deformities; Foot diseases; Quality of life; Foot